A deeper meaning for shallow‐level phylogenomic studies: nested anchored hybrid enrichment offers great promise for resolving the tiger moth tree of life (Lepidoptera: Erebidae: Arctiinae). (19th April 2020) - Dowdy, Nicolas J.; Keating, Shannon; Lemmon, Alan R.; Lemmon, Emily M.; Conner, William E.; Scott Chialvo, Clare H.; Weller, Susan J.; Simmons, Rebecca B.; Sisson, Melissa S.; Zaspel, Jennifer M.
Abstract: Anchored hybrid enrichment (AHE) has emerged as a powerful tool for uncovering the evolutionary relationships within many taxonomic groups. AHE probe sets have been developed for a variety of insect groups, though none have yet been shown to be capable of simultaneously resolving deep and very shallow (e.g., intraspecific) divergences. In this study, we present NOC1, a new AHE probe set (730 loci) for Lepidoptera specialized for tiger moths and assess its ability to deliver phylogenetic utility at all taxonomic levels. We test the NOC1 probe set with 142 individuals from 116 species sampled from all the major lineages of Arctiinae (Erebidae), one of the most diverse groups of noctuoids (>11 000 species) for which no well‐resolved, strongly supported phylogenetic hypothesis exists. Compared to previous methods, we generally recover much higher branch support (BS), resulting in the most well‐supported, well‐resolved phylogeny of Arctiinae to date. At the most shallow‐levels, NOC1 confidently resolves species‐level and intraspecific relationships and potentially uncovers cryptic species diversity within the genus Hypoprepia . We also implement a 'sensitivity analysis' to explore different loci combinations and site sampling strategies to determine whether a reduced probe set can yield results similar to those of the full probe set. At both deep and shallow levels, only 50–175 of the 730 loci included in the complete NOC1 probe set were necessary to resolve most relationships with high confidence, though only when the more rapidly evolving sites within each locus are included. This demonstrates that AHE probe sets can be tailored to target fewer loci without a significant reduction in BS, allowing future studies to incorporate more taxa at a lower per‐sample sequencing cost. NOC1 shows great promise for resolving long‐standing taxonomic issues and evolutionary questions within arctiine lineages, one of the most speciose clades within Lepidoptera. Abstract : We present NOC1, a new 730 loci anchored hybrid enrichment probe set specialized for the Noctuoidea, the largest superfamily of Lepidoptera, which simultaneously resolves deep and very shallow divergences. Using the tiger moths (Erebidae: Arctiinae) as a case study, we show that NOC1 produces the most well‐supported, well‐resolved phylogeny of Arctiinae to date, greatly outperforming previous methods. We show that fewer probe set loci can be targeted without significant reduction in phylogenetic branch support, possibly allowing more taxa to be sampled at a lower per‐taxon sequencing cost.